(xy-1)(xy+1)(x+3)=0

Simple and best practice solution for (xy-1)(xy+1)(x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (xy-1)(xy+1)(x+3)=0 equation:


Simplifying
(xy + -1)(xy + 1)(x + 3) = 0

Reorder the terms:
(-1 + xy)(xy + 1)(x + 3) = 0

Reorder the terms:
(-1 + xy)(1 + xy)(x + 3) = 0

Reorder the terms:
(-1 + xy)(1 + xy)(3 + x) = 0

Multiply (-1 + xy) * (1 + xy)
(-1(1 + xy) + xy(1 + xy))(3 + x) = 0
((1 * -1 + xy * -1) + xy(1 + xy))(3 + x) = 0
((-1 + -1xy) + xy(1 + xy))(3 + x) = 0
(-1 + -1xy + (1 * xy + xy * xy))(3 + x) = 0
(-1 + -1xy + (1xy + x2y2))(3 + x) = 0

Combine like terms: -1xy + 1xy = 0
(-1 + 0 + x2y2)(3 + x) = 0
(-1 + x2y2)(3 + x) = 0

Multiply (-1 + x2y2) * (3 + x)
(-1(3 + x) + x2y2(3 + x)) = 0
((3 * -1 + x * -1) + x2y2(3 + x)) = 0
((-3 + -1x) + x2y2(3 + x)) = 0
(-3 + -1x + (3 * x2y2 + x * x2y2)) = 0
(-3 + -1x + (3x2y2 + x3y2)) = 0
(-3 + -1x + 3x2y2 + x3y2) = 0

Solving
-3 + -1x + 3x2y2 + x3y2 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 3=7+b | | -6(-1)+2= | | (8)(15)(5)(9)= | | 12.99x=30 | | 6-3x=4x+9 | | a-15=-19 | | (1/3x)-(2/4x)=(3/4) | | 5x^3=130 | | 3(2x-2)=10+x | | (4x-12)+52=90 | | -6(0)+2= | | 3(4x+5)-5(7x-7)=2(6x+1) | | 0=x^2-9x-8 | | -(x+11)=2(2x-6) | | 5*(1/3)-(-2/3)X | | 2(6x-1)=120 | | -30=-14+v | | 4x=4(0+2x) | | 6x+68=9x-7 | | 2x+20+3x+8=180 | | -3=x-15 | | 9sin^2x+2=3 | | 2=2n | | 1x-20=10 | | b-5=-24 | | 5x+85=53 | | (36x)/(-8x) | | 2x+1=6x+(-23) | | 3k=-51 | | 3n+4=7n+4 | | 2+25x=20x+15 | | 3.4x=2.7 |

Equations solver categories